Carl Friedrich Richard Foerster (1825–1902) – the inventor of perimeter and photometer. (1st April 2015) - Grzybowski, Andrzej; Sobolewska, Bianka
Abstract Carl Friedrich Richard Foerster (1825–1902) was a German who was born in the Polish city Leszno. He studied medicine at the Medical Faculty of Breslau (now Wroclaw, Poland) University, and later in Heidelberg and Berlin. From 1855, he worked in Breslau, where he established in 1857 the first ophthalmology clinic. Later, he became a professor in ophthalmology, the first director of the Department of Ophthalmology at the University of Breslau, and even the rector of this University. Forster did many pioneering works on visual fields, invented a photometer and the first perimeter, known for many years as the Foerster perimeter. Moreover, he studied night blindness, visual field changes due to different pathologies, and many eye diseases, including glaucoma, cataract, retinal and choroidal diseases.